2017
DOI: 10.1111/jwas.12432
|View full text |Cite
|
Sign up to set email alerts
|

Immune Response and Disease Resistance of Barramundi, Lates calcarifer (Bloch), Offered Diets Supplemented with Replete Levels of Tryptophan or Whey

Abstract: A basal diet containing 45% protein, 10% lipid, and 1.95% tryptophan (Trp) was formulated, and then supplemented with crystalline Trp (0, 0.1, 0.5, and 1% of the diet) or whey (16.9%) to evaluate the physiological effects of juvenile (initial weight: 0.57 ± 0.15 g) barramundi over a 58-d rearing period. Significant reductions in growth and feed intake were observed in fish offered diets supplemented with Trp as compared to those offered the basal diet or the whey diet. Brain serotonin increased in fish fed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…By contrast, the confinement/netting stress test only resulted in an upregulation of mxp at 1hps. These results agree with a study in barramundi ( Lates calcarifer ) fed a diet supplemented with 1% Trp where there was high lysozyme activity and an upregulation of mxp expression after a challenge with nervous necrosis virus (NNV) (Chi et al., 2018). These results may be explained by the participation of interferon regulatory factors (IRF) in the regulation of the abovementioned proteins.…”
Section: Discussionsupporting
confidence: 91%
“…By contrast, the confinement/netting stress test only resulted in an upregulation of mxp at 1hps. These results agree with a study in barramundi ( Lates calcarifer ) fed a diet supplemented with 1% Trp where there was high lysozyme activity and an upregulation of mxp expression after a challenge with nervous necrosis virus (NNV) (Chi et al., 2018). These results may be explained by the participation of interferon regulatory factors (IRF) in the regulation of the abovementioned proteins.…”
Section: Discussionsupporting
confidence: 91%
“…hydrophila [ 83 ]. Similarly, improved lysosomal and phagocytic activity has been reported in response to inclusion of whey in Barramundi ( Lates calcarifer ) diets [ 84 ]. In our study, it is important to mention that an elevated immune response and higher survival were only observed in the larvae fed Diet 3 and not Diet 2, which also included whey proteins, but in much lower levels, indicating that this inclusion level might be insufficient to facilitate the same immunomodulatory effect.…”
Section: Discussionmentioning
confidence: 80%
“…Chi et al [73] reported improved lysosomal and phagocytic activity with the inclusion of whey in Barramundi, Lates calcarifer, diet. The increase in the phagocytic percentage, phagocytic index, and nitric oxide level by WPC inclusion was attributed to the stimulation of the macrophage [74], [75].…”
Section: Discussionmentioning
confidence: 99%